Single-cell transcriptomics analysis of the healing process of ligament rupture - Haibo Zhao; Jianbao Gong; Tengbo Yu; Yingze Zhang (Bone & Joint Research)
Aims: The repair process of ligament ruptures is a complex phenomenon involving three stages: early, repair, and remodelling. This study aimed to investigate the cellular and genetic aspects related to the repair and healing of ligament ruptures using single-cell RNA sequencing (scRNA-seq) on anterior cruciate ligament (ACL) tissues. Methods: A comprehensive examination was conducted on ACL tissues from three healthy individuals and three patients with ligament ruptures at different timepoints (one week, three weeks, and six months post-injury). A deep gene expression analysis was performed on 83,195 cells obtained from the six cases, and immunohistochemistry techniques were used to identify cell types. Results: In this study, tenocytes and fibroblasts in ligament tissues were distinctly identified for the first time. Moreover, a total of ten cell populations were discovered in ACL tissues, comprising tenocytes, fibroblasts, macrophages, stromal cells, T cells, endothelial cells, B cells, epithelial cells, chondrocytes, and monocytes. Further analysis of the tenocyte populations revealed ten distinct subtypes, highlighting the diversity of tenocytes in human ACL tissues. Conclusion: The identification of multiple specialized tenocyte populations in human ACL tissues sheds light on potential avenues for advancing research in cell therapy for ligament injuries. These findings provide valuable insights into the cellular components involved in the repair and healing processes of ligament ruptures, paving the way for future investigations in this field. Cite this article: Bone Joint Res 2025;14(6):539–550.